Auscultation of Velcro Crackles is Associated With Usual Interstitial Pneumonia. Issue 5 (February 2016) - Sellarés, Jacobo; Hernández-González, Fernanda; Lucena, Carmen Mª; Paradela, Marina; Brito-Zerón, Pilar; Prieto-González, Sergio; Benegas, Mariana; Cuerpo, Sandra; Espinosa, Gerard; Ramírez, José; Sánchez, Marcelo; Xaubet, Antoni
Abstract : Abstract: Auscultation of Velcro crackles has been proposed as a key finding in physical lung examination in patients with interstitial lung diseases (ILDs), especially in idiopathic pulmonary fibrosis (IPF). However, no studies have been carried out to assess the association of Velcro crackles with other clinical variables. We evaluated a cohort of 132 patients, prospectively and consecutively included in our ILD diagnostic program at a tertiary referral center. All patients were auscultated during the physical examination. The patients were divided into 2 groups: "presence" or "nonpresence" of bilateral Velcro crackles. Of all patients assessed, 83 (63%) presented Velcro crackles in the respiratory auscultation. Patients with Velcro crackles usually had more frequently cough and dyspnea at the moment of diagnosis. Forced vital capacity ( P = 0.002) and lung diffusion capacity for carbon monoxide ( P = 0.04) was lower in these patients. The ILD-GAP index was higher in the group with Velcro crackles ( P = 0.01). All patients with usual interstitial pneumonia (UIP) in high-resolution computed tomography and all patients with final IPF diagnosis presented Velcro crackles. In multivariate analysis, the presence of Velcro crackles was independently associated with an UIP pattern. In patients suspected of having ILD, the auscultation of Velcro crackles was associated with UIP, a possibility which must be taken into consideration in early ILD detection in primary care.